History, Man, & Reason A Study in Nineteenth-Century Thought - Mandelbaum, Maurice, 1908-1987.; Project Muse; Project Muse. (Project Muse, 2019)
The purpose of this book is to draw attention to important aspects of thought in the nineteenth century. While its central concerns lie within the philosophic tradition, materials drawn from the social sciences and elsewhere provide important illustrations of the intellectual movements that the author attempts to trace. This book aims at examining philosophic modes of thought as well as sifting presuppositions held in common by a diverse group of thinkers whose antecedents and whose intentions often had little in common. After a preliminary tracing of the main strands of continuity within philosophy itself, the author concentrates on how, out of diverse and disparate sources, certain common beliefs and attitudes regarding history, man, and reason came to pervade a great deal of nineteenth-century thought. Geographically, this book focuses on English, French, and German thought. Mandelbaum believes that views regarding history and man and reason pose problems for philosophy, and he offers critical discussions of some of those problems at the conclusions of parts 2, 3, and 4.
part I. Philosophical background -- 1. Philosophic movements in the nineteenth century -- part II. Historicism -- 2. The nature and scope of historicism -- 3. The first phase of historicism : from the Enlightenment through Hegel -- 4. The search for a science of society : from Saint-Simon to Marx and Engels -- 5. Evolution and progress -- 6. Social evolutionism -- 7. Historicism : a critical appraisal -- part III. The malleability of man -- 8. Challenges to constancy -- 9. Geneticism : the associationist tradition -- 10. Organicism : culture and human nature -- 11. Man as a progressive being -- 12. Constancy and change in human nature : a critical account -- part IV. The limits of reason -- 13. Critiques of the instellectual powers of man : the idealist strand -- 14. Ignoramus, ignorabimus : the positivist strand -- 15. The rebellion against reason -- 16. The limits reappraised.
Originally published Baltimore, Maryland : Johns Hopkins Press, [1971].
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Reason; History -- Philosophy; Modern philosophy -- 19th century; Electronic books; Electronic books